Diabetes-related Amylin Dyshomeostasis: a Contributing Factor to Cerebrovascular Pathology and Dementia - Ly, Han (J Lipid Atheroscler, 2019)
Type 2 diabetes (T2D) increases the risk for cerebrovascular disease (CVD) and dementia. The underlying molecular mechanisms remain elusive, which hampers the development of treatment or/and effective prevention strategies. Recent studies suggest that dyshomeostasis of amylin, a satiety hormone that forms pancreatic amyloid in patients with T2D, promotes accumulation of amylin in cerebral small blood vessels and interaction with Alzheimer's disease (AD) pathology. Overexpression of human amylin in rodents (rodent amylin does not form amyloid) leads to late-life onset T2D and neurologic deficits. In this Review, we discuss clinical evidence of amylin pathology in CVD and AD and identify critical characteristics of animal models that could help to better understand molecular mechanisms underlying the increased risk of CVD and AD in patients with prediabetes or T2D.